1999
DOI: 10.1046/j.1469-0705.1999.14030210.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of transvaginal ultrasonography and CA 125 in the preoperative evaluation of myometrial invasion in endometrial carcinoma

Abstract: Objective To compare the ability of transvaginal sonography and serum CA 125 levels to predict myometrial invasion in patients with endometrial carcinoma. (30 IU/ml, interquartile range (IQR) 46.0 vs. 16.9 IU/ml, IQR 13.9, respectively; p = 0.002). The sensitivity, specificity, respectively. The sensitivity, specificity, and Design and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Some groups (13,(21)(22)(23)(24)(25)(26) have assessed the role of transvaginal twodimensional (2D) ultrasonography (US) for the assessment of myometrial invasion with considerable variation in methods and results. This could be explained by the fact that this technique is highly operator dependent because it is mainly based on the subjective impression of the examiner.…”
mentioning
confidence: 99%
“…Some groups (13,(21)(22)(23)(24)(25)(26) have assessed the role of transvaginal twodimensional (2D) ultrasonography (US) for the assessment of myometrial invasion with considerable variation in methods and results. This could be explained by the fact that this technique is highly operator dependent because it is mainly based on the subjective impression of the examiner.…”
mentioning
confidence: 99%
“…As a conclusion, in order to prevent from the noted medical errors it is suggested to use combined method including immunoassay, Doppler colorful ultrasonography [5] and transvaginal ultrasonography [6]. Immunoassay method in turn should be consisted of dual assaying CA-125 and CEA, because it might be helpful to distinguish endometriosis (stage 3 and 4) from ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Other than endometriosis, other cases such as septicemia secondary to E. coli also can result in up-regulation of CA-125 [1]. Also in endometrial carcinoma which is one of the most commonplace malignancies in women we have up-regulation of CA-125 [6].…”
mentioning
confidence: 99%
“…In their study, Alcazer JL et al [25] evaluated the relationship between serum CA 125 levels and myometrial invasion depth in 50 endometrial cancer patients and found the CA 125 levels to be higher in patients with deep invasion. Choi et al [26] reported the preoperative CA 125 level to be significantly associated with deep myometrial invasion in 42 endometrial cancer patients.…”
Section: Discussionmentioning
confidence: 99%